TI_GERICHTE 15.2006.85 vom 2. Januar 2007 , Pignoramenti nulli. Minimo d'esistenza. Spese alloggio. Assegni di famiglia. Mutate circostanze. - TI Tribunale d'appello (2007)
Pignoramenti nulli. Minimo d'esistenza. Spese alloggio. Assegni di famiglia. Mutate circostanze.